(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2013)
Public budget is the government’s tool in achieving the objectives of economic and social development is the accounting curriculum to estimate state revenues and expenditures for years to come, as well as to have legal status as it is after the adoption of an official statement of government units to spend funds on items planned at the same time is a statement collect resources to finance these appropriations, if the primary objective of the budget initially limited to the achievement of financial and legislative control have evolved this function in the area of public administration turned attention from mere imposition of control over the money, which provides information to assist the Department to utilize available resources and programs to achieve efficient, effective and economic link between inputs ( expenditure) and output (objectives achieved); it took give the rationale of the appropriation request is when you view the budget on the legislative authority is linked to programs and activities to be performed by government regulations during the period of the budget. The increased government activity and responsibilities of the State showed a defect in the government accounting system and the traditional balance in the provision of information to support management strategy showed the need to reform the budget system have yet to include elements of strategic planning and management efficiency in the completion of the work and the optimal use of resources, the wording of the strategic concept of the interest must be the governmental unit to study the external environment to identify opportunities, risks and potential internal study to determine the strengths and weaknesses and the need to develop accounting systems to provide information appropriate to the decision-making advanced, the complexity of the work environment in public administration, which required the expansion of the accounting information provided by the output of what the government accounting system using a system of management accounting strategy tend to focus on the future provision of external information to support management and the adoption of strategic planning, programming and budget, the best source of information on the budget and clearly understood by local governments, linking strategic planning and budget preparation for a sophisticated system support load balancing contractual shift budget to projects with four dimensions of work and specifications and the time required for completion and cost of speculative finance and this is what facilitates the process of implementation and control and is efficient in performance between funds being earmarked and objectives. Goal of establishing local governments based on the principle of administrative decentralization is to provide services and the establishment of infrastructure projects as not only the funding for these projects to assignments of the general budget, but may be through loans or participation with the private sector, create a way BOT. The financial reports prepared by government units must meet the requirements of the minimum financial statements identified by the Governmental Accounting Standards Board and such reports are comprehensive and cover the funds all government activities including disclosure required and a commitment to accepted accounting principles and standards. States have adopted the modern system of administrative decentralization is the transfer of responsibility for planning and funding of public services and management to local government and under the responsibility accounting system can achieve control depending on the budget system as a low cost, timing and quality measures